2021
DOI: 10.3389/fevo.2021.763191
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Temperatures and Heat Wave on Thermal Biology, Locomotor Performance, and Antioxidant System of High-Altitude Frog Nanorana pleskei Endemic to Qinghai-Tibet Plateau

Abstract: Investigating how highland amphibians respond to changes in ambient temperature may be of great significance for their fate prediction and effective conservation in the background of global warming. Here, using field individuals as the control group, we investigated the influence of high temperatures (20.5 and 25.5°C) and heat wave (15–26.6°C) on the thermal preference, critical thermal limits, locomotor performance, oxidative stress, and antioxidant enzyme activities in high-altitude frog Nanorana pleskei (3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…This phenomenon indicated that at 27 °C, frog body cells produced higher levels of hydrogen peroxide than at other environmental temperatures. The results of this study are consistent with the findings of He et al [ 26 ], who reported that exposure to high temperature environments and heat waves increased hydrogen peroxide levels in both the liver and muscle of Nanorana pleskei frogs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This phenomenon indicated that at 27 °C, frog body cells produced higher levels of hydrogen peroxide than at other environmental temperatures. The results of this study are consistent with the findings of He et al [ 26 ], who reported that exposure to high temperature environments and heat waves increased hydrogen peroxide levels in both the liver and muscle of Nanorana pleskei frogs.…”
Section: Discussionsupporting
confidence: 93%
“…The antioxidant system generally consists of enzymatic antioxidants, such as catalase, glutathione peroxidase, glutathione reductase, and superoxide dismutase, as well as non-enzymatic antioxidants, such as glutathione etc. [ 26 ]. The measure of total antioxidant power can be determined using all the antioxidants which were present in samples [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold acclimation reduces antioxidant defense in N. pleskei [ 32 ]. However, N. pleskei may have well adapted to the significant temperature fluctuation, according to a study on the impact of high temperatures and heat waves on thermal biology, locomotor performance, and antioxidant system [ 33 ]. The range of tolerated temperature, thermal preference, and critical thermal maximum all dramatically increased after two weeks of heat wave acclimation, whereas the critical thermal minimum significantly dropped [ 33 ].…”
Section: Introductionmentioning
confidence: 99%